I am Sammy, trusted guide - Stier, Catherine; Rosa, Francesca (Chicago, Illinois : Albert Whitman & Company, 2021)
Sammy, a golden retriever, becomes a guide dog for Jessie, a college freshman who is blind, and constantly watches their big-city surroundings to keep her safe. Includes back matter about the breed and the role of the working dog.
Ages 7-12.
Grades 4-6.
Keywords: Golden retriever -- Juvenile fiction; Golden retriever -- Fiction; Guide dogs -- Fiction; Working dogs -- Fiction